2011
DOI: 10.1016/j.ejcnurse.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Disease and Its Consequences on the Partner Relationship: A Systematic Review

Abstract: The review found that though couples found the cardiac event distressful they conformed and adjusted their relationship to the new situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
2
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 64 publications
11
107
2
7
Order By: Relevance
“…Of course, we realize that having a partner is strongly associated with the perception of sexual problems because patients who have a partner can be expected to be confronted more often with those problems as part of their daily life. 23 However, our study also showed that 18% of the patients who perceived difficulties with sexual activity were living without a partner; thus, not only patients with a partner experience sexual difficulties caused by HF that prevent them from living as they want. It is important to report the prevalence in dysfunction in both patients with and without a partner because patients might define sexual activity broader than having intercourse (eg, masturbation) and single patients might worry about their (future) sex life.…”
Section: Discussionmentioning
confidence: 57%
“…Of course, we realize that having a partner is strongly associated with the perception of sexual problems because patients who have a partner can be expected to be confronted more often with those problems as part of their daily life. 23 However, our study also showed that 18% of the patients who perceived difficulties with sexual activity were living without a partner; thus, not only patients with a partner experience sexual difficulties caused by HF that prevent them from living as they want. It is important to report the prevalence in dysfunction in both patients with and without a partner because patients might define sexual activity broader than having intercourse (eg, masturbation) and single patients might worry about their (future) sex life.…”
Section: Discussionmentioning
confidence: 57%
“…Given that caregiver strain was lowest in this type of dyad despite significant contributions to self-care and the worst patient QOL, the high reports of relationship quality indicate the collaboration in this type of dyad is likely based on cooperation, shared decision-making and a mutual understanding of how best to work together (Rohrbaugh et al, 2008;Sebern and Riegel, 2009;Sebern and Woda, 2012). Communication problems are a known source of stress for heart failure families (Dalteg et al, 2011;Luttik et al, 2007a,b), and positive communication is associated with greater confidence in heart failure self-care (Sebern and Riegel, 2009). Thus, it may be that better relationship quality and effective communication mitigates the influence that poor patient QOL would otherwise have on caregiver strain in this type of heart failure dyad.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that a study undertaken with heart disease patients for evaluating the effectiveness of a nursing educational program on the improvement of self- care behaviors in patients with heart failure determined that educational gatherings, home visits, tele-nursing and printed booklets have a beneficial effect on the process of compliance and maintenance of treatment (20) .…”
Section: According To Research Carried Out In the Cardiacmentioning
confidence: 99%